2017
DOI: 10.1111/jeb.13096
|View full text |Cite
|
Sign up to set email alerts
|

Costs and benefits of sublethal Drosophila C virus infection

Abstract: Viruses are major evolutionary drivers of insect immune systems. Much of our knowledge of insect immune responses derives from experimental infections using the fruit fly Drosophila melanogaster. Most experiments, however, employ lethal pathogen doses through septic injury, frequently overwhelming host physiology. While this approach has revealed several immune mechanisms, it is less informative about the fitness costs hosts may experience during infection in the wild. Using both systemic and oral infection ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
59
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 74 publications
3
59
2
Order By: Relevance
“…We found qualitatively similar effects of DCV infection on both fecundity and 373 mortality (when controlling for the effects of vial transfers on our flies) as past 2 (37) found that the response to DCV infection depended on host genotype with some 376 genotypes responding to infection with a decrease and others with an increase in 377 fecundity. Previous work on fly survival that has used oral challenge of DCV has found 378 increased mortality soon after exposure (38), and our survival results match the morality 379 rates estimated by Ferreira et al (18).…”
Section: (A)fecundity 277supporting
confidence: 73%
See 1 more Smart Citation
“…We found qualitatively similar effects of DCV infection on both fecundity and 373 mortality (when controlling for the effects of vial transfers on our flies) as past 2 (37) found that the response to DCV infection depended on host genotype with some 376 genotypes responding to infection with a decrease and others with an increase in 377 fecundity. Previous work on fly survival that has used oral challenge of DCV has found 378 increased mortality soon after exposure (38), and our survival results match the morality 379 rates estimated by Ferreira et al (18).…”
Section: (A)fecundity 277supporting
confidence: 73%
“…In contrast, Gupta et al (37) found that inoculation of DCV did not increase mortality 385 relative to unexposed flies, a result that could be explained by their use of a lower viral 386 dosage than the one used in our study or by differences in the density flies were kept at 387 post virus exposure (their flies were kept in isolation). 388…”
Section: (A)fecundity 277contrasting
confidence: 71%
“…We investigated the effect of dietary protein on terminal investment in response to infection, a form of nonimmunological defence that mitigates the potential fitness losses of infection by increasing reproductive investment (Kutzer & Armitage, 2016a;Parker et al, 2011). We found that oral infection by P. aeruginosa was sufficient to trigger a shift in reproductive investment, recapitulating similar increases in reproductive output in D. melanogaster following sub-lethal viral infections (Gupta, Stewart, et al, 2017). Given the elevated protein requirements of oogenesis (Mirth et al, 2019), we hypothesized that terminal investment would be more likely to be observed when protein was not limited.…”
Section: Discussionmentioning
confidence: 99%
“…Terminal investment may take the form of increased early reproductive output, early maturation or an increase in other forms of reproductive investment such as mating effort or parental care (Duffield, Bowers, Sakaluk, & Sadd, 2017). Terminal investment has been observed in diverse animal and plant taxa in response to a wide range of cues (reviewed in Duffield et al, 2017), including resource availability (Kim & Donohue, 2011), injury (Morrow, Arnqvist, & Pitnick, 2003), nonpathogenic immune stimulation (Bonneaud, Mazuc, Chastel, Westerdahl, & Sorci, 2004;Jacot, Scheuber, & Brinkhof, 2004) and infection by lethal (Gupta, Stewart, Rund, Monteith, & Vale, 2017;Waldman, An, & Waldman, 2016), sub-lethal (Gupta, Stewart, et al, 2017;Roznik, Sapsford, Pike, Schwarzkopf, & Alford, 2015) or sterilizing (Chadwick & Little, 2005;Minchella & Loverde, 1981;Vale & Little, 2012) pathogens. Because it increases host fitness during infection without directly reducing pathogen burdens, terminal investment increases host disease tolerance and has been described as an adaptive, nonimmunological defence against infection (Kutzer & Armitage, 2016a;Parker, Barribeau, Laughton, Roode, & Gerardo, 2011).…”
mentioning
confidence: 99%
“…The only virus family we found in associated with D. suzukii that has any history as a control agent (Zeddam et al, 2003, Peng et al, 1998, Peng et al, 2000 is the reovirus 'Eccles virus'. Eccles virus was relatively rare in our samples, but this may speak to the potential pathogenicity of the virus, as flies harbouring a particularly pathogenic virus, especially one that has a short latency period, may be less likely to visit baited traps (Gupta et al, 2017). Further investigation of this virus, including isolation and pathogenicity assays, are needed before any further conclusions can be drawn about its utility as a control agent.…”
Section: Discussionmentioning
confidence: 95%